The Role of Integrated Marketing Communication in SMA Thursina IIBS - Brennadiva, Allodia Astried; Wono, Hilda Yunita (Indonesian Journal of Social Science Research, 2025)
This study examines the implementation of Integrated Marketing Communication (IMC) strategies at SMA Thursina IIBS Malang, a private Islamic boarding school that combines traditional boarding school values with international education standards. In Indonesia, where the majority of the population is Muslim, religious-based boarding schools have become a significant educational option. SMA Thursina IIBS Malang stands out for its ability to integrate Islamic values with a globally competitive curriculum, making it an attractive choice for many parents. The main objective of this research is to identify and evaluate the IMC elements used by the school to attract prospective students’ parents, with a focus on how tools such as advertising, public relations, personal selling, direct marketing, and digital or social media promotion are strategically coordinated to support the institution’s marketing goals. Using a quasi-qualitative case study approach, this research gathers data through structured interviews with key stakeholders, including school leaders, public relations personnel, and both current and prospective parents. The findings are expected to offer valuable insights into how IMC can be effectively applied in a specialized educational context, particularly in Islamic boarding schools with international standards. Furthermore, the study aims to provide practical recommendations for SMA Thursina IIBS Malang to strengthen its marketing communication strategy and serve as a reference model for similar institutions across Indonesia.